Diseño de un prototipo de prótesis robótica antropomórfica de mano utilizando BCI no invasivo y percepción de temperatura mediante sensores - Molina Guadalupe, Cristian Marcelo (2024)
In the present project, an initial model of a prosthesis was developed, utilizing 3D printing technology as a non-intrusive alternative for individuals with upper limb amputations, specifically below the elbow. The operation of this device is based on receiving endogenous signals generated by the user's EEG waves, enabling the control of hand flexion and extension movements. Additionally, it provides the sensation of temperature through color indicators. This work was carried out in three phases; in the first phase, a study was conducted on different types of brain-computer interfaces and existing technologies. In the second phase, the prosthesis prototype was designed, assembled, and implemented, and in the final phase, functionality tests were conducted. The prototype's operation was evaluated concerning the user's position effect and the waiting time to execute the command, in the number of correct executions when performing flexion and extension instructions. The main result determined that the user's position, whether seated or standing, has no effect on the number of correct executions, while the waiting time does have an effect. The time with the lowest number of correct executions was 5 seconds, with 22 out of 30, compared to 10 and 15 seconds with 26 out of 30. Similarly, the data from the temperature perception system were compared with those measured by a commercial thermometer, resulting in statistically equal averages.